Latin American Student Movements in the 1960s - Luciani, Laura Luján (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article examines student movements in Argentina, Mexico and Brazil in the 1960s from a predominantly Latin American perspective. We concentrate on student experiences of the selected countries, their common strategies, bonds, networks, and the history of their struggle throughout the XX century. We highlight the massive and meaningful movements of 1968 and 1969, focusing on common points of analysis, such as the tension/articulation between democratizing and revolutionary proposals, anti-establishment positions regarding dialogue, the emergence of new forms of participation, radicalization, transformative proposals, as well as the ways in which State repression has been exerted, and some particularities of the different student movements of this time period.